Empirical and biophysical estimations of human cochlea’s psychophysical tuning curve sharpness - Chan, Wei Xuan (2016)
Despite the advances in cochlear research, the estimation of auditory nerve fiber frequency tuning of human cochlea is mostly based on psychophysicalmeasurements. Although efforts had been made to estimate human frequency tuning sharpness from various physiological measurements which are less species dependent such as the compound action potential and stimulus-frequency otoacoustic emission delay, conclusions on the relative frequency tuning sharpness compared with that of other mammals vary. We simulated the biophysical human cochlea’s tuning curve based on physiological measurements of human cochlea and compared the human frequency tuning sharpness with results from empirical methods as well as experimental data of other mammalian cochleae. The compound action potential are more accurate at frequencies below 3 kHz while the stimulus frequency-otoacoustic emission delay are more accurate at frequencies above 1 kHz regions. The results from mechanical cochlearmodels, with support from conclusions of the other two empirical methodologies, suggest that the human frequency tuning sharpness at frequencies below 1 kHz is similar to common laboratory mammals but is exceptionally sharp at higher frequencies.